Saharan dust – a carrier of persistent organic pollutants, metals and microbes to the Caribbean? - Garrison, V. H.; Foreman, W. T.; Genualdi, S.; Griffin, D. W.; Kellogg, C. A.; Majewski, M. S.; Mohammed, A.; Ramsubhag, A.; Shinn, E. A.; Simonich, S. L.; Smith, G. W. (Revista de Biología Tropical, 2006)
An international team of scientists from government agencies and universities in the United States, U.S. Virgin Islands (USVI), Trinidad & Tobago, the Republic of Cape Verde, and the Republic of Mali (West Africa) is working together to elucidate the role Saharan dust may play in the degradation of Caribbean ecosystems. The first step has been to identify and quantify the persistent organic pollutants (POPs), trace metals, and viable microorganisms in the atmosphere in dust source areas of West Africa, and in dust episodes at downwind sites in the eastern Atlantic (Cape Verde) and the Caribbean (USVI and Trinidad & Tobago). Preliminary findings show that air samples from Mali contain a greater number of pesticides, polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs) and in higher concentrations than the Caribbean sites. Overall, POP concentrations were similar in USVI and Trinidad samples. Trace metal concentrations were found to be similar to crustal composition with slight enrichment of lead in Mali. To date, hundreds of cultureable microorganisms have been identified from Mali, Cape Verde, USVI, and Trinidad air samples. The sea fan pathogen, Aspergillus sydowii, has been identified in soil from Mali and in air samples from dust events in the Caribbean. We have shown that air samples from a dust-source region contain orders of magnitude more cultureable microorganisms per volume than air samples from dust events in the Caribbean, which in turn contain 3-to 4-fold more cultureable microbes than during non-dust conditions. Rev. Biol. Trop. 54 (Suppl. 3): 9-21. Epub 2007 Jan. 15.